HOPES: INDONESIAN GOOD WATER QUALITY AS AN IDEA FOR PAINTING ART CREATIONS - Arum Wilis Kartika Ayuningtari; Rizal Wahyu Bagas Pradana (UPT Pusat Penerbitan LP2MPP ISI Bali, 2022)
This research aims to create artwork with ideas originating from an actual phenomenon regarding the poor quality of river water and the contamination of beaches and seas due to factory waste and garbage in Indonesia. Water is a basic human need such as for consumption, bathing, irrigating fields, and other activities. Based on this, water quality really needs to be maintained for the survival of a higher-quality human being. The data is obtained through documents and literature studies. This research used a combination method of practice-based research and practice-led research method. This research produces a two-dimensional painting that is representational-deformative and has symbolic meanings. This painting uses pop-surrealism style and acrylic on plywood media. This artwork visualizes the writer's hopes about the quality of Indonesian rivers and seas that will improve in the future so that our children and grandchildren can enjoy its beauty. This creation is useful as a medium of criticism and as a medium of education to society related to the phenomenon or topic of water pollution in Indonesian territory. This phenomenon should be aware of and must be fixed immediately to reduce the negative impact that is harming the environment.